MondoA drives malignancy in B-ALL through enhanced adaptation to metabolic stress - Sipol, Alexandra; Hameister, Erik; Xue, Busheng; Hofstetter, Julia; Barenboim, Maxim; Öllinger, Rupert; Jain, Gaurav; Prexler, Carolin; Rubio, Rebeca Alba; Baldauf, Michaela C.; Franchina, Davide G.; Petry, Andreas; et al. (Blood, 2022)
Cancer cells are in most instances characterized by rapid proliferation and uncontrolled cell division. Hence, they must adapt to proliferation-induced metabolic stress through intrinsic or acquired antimetabolic stress responses to maintain homeostasis and survival. One mechanism to achieve this is reprogramming gene expression in a metabolism-dependent manner. MondoA (also known as Myc-associated factor X-like protein X-interacting protein [MLXIP]), a member of the MYC interactome, has been described as an example of such a metabolic sensor. However, the role of MondoA in malignancy is not fully understood and the underlying mechanism in metabolic responses remains elusive. By assessing patient data sets, we found that MondoA overexpression is associated with worse survival in pediatric common acute lymphoblastic leukemia (ALL; B-precursor ALL [B-ALL]). Using clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (Cas9) and RNA-interference approaches, we observed that MondoA depletion reduces the transformational capacity of B-ALL cells in vitro and dramatically inhibits malignant potential in an in vivo mouse model. Interestingly, reduced expression of MondoA in patient data sets correlated with enrichment in metabolic pathways. The loss of MondoA correlated with increased tricarboxylic acid cycle activity. Mechanistically, MondoA senses metabolic stress in B-ALL cells by restricting oxidative phosphorylation through reduced pyruvate dehydrogenase activity. Glutamine starvation conditions greatly enhance this effect and highlight the inability to mitigate metabolic stress upon loss of MondoA in B-ALL. Our findings give novel insight into the function of MondoA in pediatric B-ALL and support the notion that MondoA inhibition in this entity offers a therapeutic opportunity and should be further explored.
Gesehen am 02.02.2023